Sodium-glucose cotransporter 2 inhibitor dapagliflozin prevents ejection fraction reduction, reduces myocardial and renal NF-κB expression and systemic pro-inflammatory biomarkers in models of short-term doxorubicin cardiotoxicity - Quagliariello, V.; Canale, M. L.; Bisceglia, I.; Iovine, M.; Paccone, A.; Maurea, C.; Scherillo, M.; Merola, A.; Giordano, V.; Palma, G.; Luciano, A.; Bruzzese, F.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Anthracycline-mediated adverse cardiovascular events are among the leading causes of morbidity and mortality in patients with cancer. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) exert multiple cardiometabolic benefits in patients with/without type 2 diabetes, chronic kidney disease, and heart failure with reduced and preserved ejection fraction. We hypothesized that the SGLT2i dapagliflozin administered before and during doxorubicin (DOXO) therapy could prevent cardiac dysfunction and reduce pro-inflammatory pathways in preclinical models. Methods Cardiomyocytes were exposed to DOXO alone or combined with dapagliflozin (DAPA) at 10 and 100 nM for 24 h; cell viability, iATP, and Ca++ were quantified; lipid peroxidation products (malondialdehyde and 4-hydroxy 2-hexenal), NLRP3, MyD88, and cytokines were also analyzed through selective colorimetric and enzyme-linked immunosorbent assay (ELISA) methods. Female C57Bl/6 mice were treated for 10 days with a saline solution or DOXO (2.17 mg/kg), DAPA (10 mg/kg), or DOXO combined with DAPA. Systemic levels of ferroptosis-related biomarkers, galectin-3, high-sensitivity C-reactive protein (hs-CRP), and pro-inflammatory chemokines (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, IL17-α, IL-18, IFN-γ, TNF-α, G-CSF, and GM-CSF) were quantified. After treatments, immunohistochemical staining of myocardial and renal p65/NF-kB was performed. Results DAPA exerts cytoprotective, antioxidant, and anti-inflammatory properties in human cardiomyocytes exposed to DOXO by reducing iATP and iCa++ levels, lipid peroxidation, NLRP-3, and MyD88 expression. Pro-inflammatory intracellular cytokines were also reduced. In preclinical models, DAPA prevented the reduction of radial and longitudinal strain and ejection fraction after 10 days of treatment with DOXO. A reduced myocardial expression of NLRP-3 and MyD-88 was seen in the DOXO-DAPA group compared to DOXO mice. Systemic levels of IL-1β, IL-6, TNF-α, G-CSF, and GM-CSF were significantly reduced after treatment with DAPA. Serum levels of galectine-3 and hs-CRP were strongly enhanced in the DOXO group; on the other hand, their expression was reduced in the DAPA-DOXO group. Troponin-T, B-type natriuretic peptide (BNP), and N-Terminal Pro-BNP (NT-pro-BNP) were strongly reduced in the DOXO-DAPA group, revealing cardioprotective properties of SGLT2i. Mice treated with DOXO and DAPA exhibited reduced myocardial and renal NF-kB expression. Conclusion The overall picture of the study encourages the use of DAPA in the primary prevention of cardiomyopathies induced by anthracyclines in patients with cancer.